Political Science Research Methods in Action
X, 261 p.
Keywords: Through accounts from innovative research projects by world-leading political scientists, this volume offers a unique perspective on research methodology. It discusses the practical and intellectual dilemmas researchers face throughout the research process in a wide range of fields from implicit attitude testing to media analysis and interviews.